2020
DOI: 10.32734/ijnpc.v2i01.3579
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Stage of Nasopharyngeal Carcinoma With Anemia and Nutritional Status in West Nusa Tenggara General Hospital

Abstract: Introduction: Nasopharyngeal carcinoma is the most common malignant tumor in the ENT-HNS were the highest of all malignant tumors of the head and neck. Malnutrition and cachexia is a common problem in cancer patients and impact on quality of life and survival. Anemia is a major problem in patients with nasopharyngeal cancer receiving chemotherapy or radiotherapy. Objective: Determine the relationship of nasopharyngeal carcinoma stage with anemia and nutritional status. Material and meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Some studies show that higher a person's BMI gives a higher life expectancy. 13,14 Based on the risk factors for the occurrence of NPC, the risk factors examined in this study such as smoking habits were found in 9 people (60%), followed by salted fish consumption in 7 people (46.7%) and alcohol consumption in 1 person (6.7%). According to Salehiniya, et al, some of the risk factors that are strongly associated with causing NPC were EBV infection, genetics, HLA genes, and salted fish consumption.…”
Section: Discussionmentioning
confidence: 86%
“…Some studies show that higher a person's BMI gives a higher life expectancy. 13,14 Based on the risk factors for the occurrence of NPC, the risk factors examined in this study such as smoking habits were found in 9 people (60%), followed by salted fish consumption in 7 people (46.7%) and alcohol consumption in 1 person (6.7%). According to Salehiniya, et al, some of the risk factors that are strongly associated with causing NPC were EBV infection, genetics, HLA genes, and salted fish consumption.…”
Section: Discussionmentioning
confidence: 86%